Clothing-related needs in disaster risk reduction management of typhoon disasters a case study in Legazpi City, Albay, Philippines - Picart, Patricia Marie Paloma LB (College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The aim of the research is to determine clothing-related needs of both disaster response personnel (DRP) and community members (CM) in the four stages of Disaster Risk Reduction Management (DRRM): mitigation, preparation, response, and recovery. The study is an exploratory research that aimed to identify clothing-related needs. It is a case study on the DRRM in Legazpi City, Albay. It conducted two personal interviews: Phase 1 involved nine DRP (such as DSWD, OCD, Red Cross, APSEMO, and LGUs) while Phase 2 involved 26 CM consisting of mothers, fathers, children, elderly as well as Barangay Captains, Kagawads, and a Health Worker. They were studied because they were the most vulnerable groups during disasters. The research found both clothing and non-clothing related needs. The study was able to determine that the physiological clothing- related needs are the one the needs the most attention. These physiological needs are important to address in order to build resilience to disasters in DRRM. The clothing-related needs arises depending on the role of the person in DRRM. The DRP oversees evacuation procedures and ensures the safety of the community. They work in extreme weather conditions that may endanger their lives. It was found that they need clothing to equip them to perform their tasks efficiently, to protect them from hazards, and to keep them comfortable during search and rescue missions and cleanup operations. The CM are exposed to bacteria and hazards due to the typhoon and therefore need clothing for protection with anti-bacterial properties. Donated clothing for CM also needs proper sanitation as well as sorting in terms of size and quality. Based on the findings, the research recommends to further evaluate the suit for contaminated water diving and the suit used by DOH in DRRM.